IMPLEMENTASI MANAJEMEN MUTU PENDIDIKAN DALAM MENINGKATKAN PRESTASI BELAJAR DI SMPN 17 MESUJI - Dino Krama Wijaya (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the implementation of educational quality management in improving student learning achievement at SMPN 17 Mesuji. The research focuses on planning, implementation, evaluation, and follow-up of quality management, along with supporting and inhibiting factors. The study employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation involving the principal, teachers, and educational staff. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal that educational quality management at SMPN 17 Mesuji has been implemented but remains suboptimal. Program planning has been aligned with the school's vision and mission; however, it has not yet been supported by measurable strategies. Program implementation still faces constraints related to limited human resources, inadequate infrastructure, and insufficient teacher training. Evaluation is conducted periodically through supervision and learning outcome assessments, but it has not yet been carried out systematically and continuously. Follow-up actions are undertaken through program improvements and instructional enhancements, although their implementation still requires strengthening. Student learning achievement has demonstrated improvement, although it has not been evenly distributed. Supporting factors include the principal's commitment and collaboration among teachers, while inhibiting factors include limited facilities, uneven teacher competence, and low parental participation. This study concludes that improving educational quality requires strengthening teacher competence, school management systems, infrastructure, and community involvement.